2014
DOI: 10.17576/jem-2014-4802-04
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Mempengaruhi Tahap Keyakinan Agihan Zakat:Kajian Terhadap Masyarakat Islam di Selangor

Abstract: Studies on the satisfaction and public confidence toward the quality of zakat distribution by the zakat institutions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Exceptional customer service becomes a benchmark for evaluating the overall performance of an organization. Wahid and Ahmad (2014) emphasize the importance of empathy and responsiveness in providing service and hospitality. Empathetic behaviour involves caring for individuals and offering personalized attention, while responsiveness denotes the willingness to help customers promptly.…”
Section: Generosity In Advice and Counsellingmentioning
confidence: 99%
“…Exceptional customer service becomes a benchmark for evaluating the overall performance of an organization. Wahid and Ahmad (2014) emphasize the importance of empathy and responsiveness in providing service and hospitality. Empathetic behaviour involves caring for individuals and offering personalized attention, while responsiveness denotes the willingness to help customers promptly.…”
Section: Generosity In Advice and Counsellingmentioning
confidence: 99%
“…It has been widely indicated that the contribution of zakat should have direct socio-economic benefits for the as . n af (Embong et al, 2013;Wahid and Ahmad, 2014;Omar et al, 2017;Shaikh and Ismail, 2017). Such benefits include but are not restricted to: cash for daily needs, capital for business start-up, education funds and others.…”
Section: Root Of Zakat In Islammentioning
confidence: 99%
“…The proper implementation of zakat could elevate the ummah ’s socio-economic standing (Firmansyah, 2013; Debnath, 2015; Romdhoni, 2017; Ayuniyyah et al , 2018; Nahar, 2018). It has been widely indicated that the contribution of zakat should have direct socio-economic benefits for the aṣnāf (Embong et al , 2013; Wahid and Ahmad, 2014; Omar et al , 2017; Shaikh and Ismail, 2017). Such benefits include but are not restricted to: cash for daily needs, capital for business start-up, education funds and others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated a problem of inefficiency in relation to the distribution of zakat recipients, giving rise to a negative perception of the zakat institution (Saad & Abdullah, 2014). In relation to this, it was reported that about 57.1% of tax payers were not satisfied with zakat institution especially in the distribution of alms to the needy (Ahmad & Wahid, 2005a;Wahid & Ahmad, 2014). In short, zakat payers' perception on the distribution efficiency will determine the level of trust towards zakat institutions.…”
Section: Perception On Distribution Of Zakatmentioning
confidence: 99%